Trends and future scenarios of forestry and other land uses employment in Indonesia: a modeling approach - Purnomo, H. (2006)
Environmental sustainability and poverty are some of the most important targets in the United Nations Millenium Development Goals. However, the relationship between employment and forestry development is unclear, especially when it comes to illegal logging. This study aims to generate projections for forestry and other land use in Indonesia and develop policy scenarios to decrease unemployment and improve environmental sustainability by examining natural forests, logging, forest plantation, wood-based industries and trade. The study observes the components of natural forest, logging, forest plantation, wood-based industries and trade. The study uses systems dynamic to implement a model of interaction among forest structure industries, actors and their institutions. The study finds that the current practice of forest management will experience growth in employment before it collapses, starting with Riau followed by East Kalimantan and Papua. Massive forest planting will benefit deforested land, but may jeopardize employment and livelihoods in community land. Land tenure reform can boost the employment to meet the overall government target on unemployment level of 5.11% in year 2009.